ANTIMICROBIAL, WOUND HEALING AND ANTIOXIDANT ACTIVITIES OF ANTHOCEPHALUS CADAMBA - Umachigi, Sanjay Prahalad; Kumar, G. S.; Jayaveera, K. N.; Kishore, D. V. Kumar; Ashok kumar, C K.; Dhanapal, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Anthocephalus cadamba (Roxb.) Miq. Syn A. chinensis (Lamk) A. Rich (Rubiaceae) is ethnomedicinally widely used in the form of paste by tribe in western Ghats for treating skin diseases. In this context, antimicrobial potential of A. cadamba against a wide range of microorganisms was studied. To validate the ethnotherapeutic claims of the plant in skin diseases, wound healing activity was studied, besides antioxidant activity to understand the mechanism of wound healing. The alchoholic and aqueous extract of this plant showed significant antibacterial and antifungal activity against almost all the organisms: Micrococcus luteus, Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa, and four fungi Candida albicans, Trichophyton rubrum—dermatophyte fungi, Aspergillus niger, Aspergillus flavus and Aspergillus nidulans—systemic fungi, with especially good activity against the dermatophyte (Trichophyton rubrum) and some infectious bacteria (Escherichia coli, Proteus mirabilis and Staphylococcus aureus) with an MIC of 2.5 µg/disc. The results show that A. cadamba extract has potent wound healing capacity as shown from the wound contraction and increased tensile strength. The results also indicated that A. cadamba extract possesses potent antioxidant activity by inhibiting lipid peroxidation and increase in the superoxide dismutase (SOD) and catalase activity.